Mumps: a rare cause of pancreatitis - Mohamed Shukor, Ahmad Zulkifli; Zainulabid, Ummu Afeera (International Journal of Human and Health Sciences (IJHHS), 2021)
Acute pancreatitis related to mumps infection is rarely reported. In this case report, wehighlight a case of acute pancreatitis caused by mumps infection in adulthood. A 25-year old woman treated for mumps developed sudden onset of vomiting and epigastric pain. She had an elevation of serum amylase and was treated for acute pancreatitis. She showed remarkable improvement of clinical symptoms with supportive treatment and after her bilateral parotid swelling receded.